2023
DOI: 10.1111/icad.12633
|View full text |Cite
|
Sign up to set email alerts
|

Woody encroachment affects multiple dimensions of ant diversity in a neotropical savanna

Abstract: Although savanna woody encroachment has become a global phenomenon, few studies have simultaneously evaluated its effects on multiple dimensions and levels of savanna biodiversity.We evaluated how the progressive increase in tree cover in a fire-suppressed savanna landscape affects the taxonomic, functional, and phylogenetic diversity of neotropical ant communities. We sampled ants along an extensive tree cover gradient, ranging from open savannas to forests established in former savanna areas due to fire supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(118 reference statements)
0
2
1
Order By: Relevance
“…However, unlike the species richness index, the difference in the average abundance of butterflies in our study was not associated with any recorded environmental factors across habitats. This is surprising because previous studies have indicated that arthropod communities vary in composition based on factors assessed in this study, such as humidity (Hamřík et al, 2023;Pelini et al, 2014) or density of vegetation (Neves et al, 2023;Pendleton et al, 2011), providing evidence that different mechanisms in heterogeneous landscapes shape different arthropod groups. Perhaps, the difference in abundance of these fruit-feeding butterflies may be associated with other habitat characteristics, such as canopy coverage (Hendy et al, 2020;McCabe et al, 2019), which likely differs throughout heterogeneous urban landscapes.…”
Section: Impact Of Landscape Heterogeneity On Frugivorous Butterfly C...contrasting
confidence: 54%
“…However, unlike the species richness index, the difference in the average abundance of butterflies in our study was not associated with any recorded environmental factors across habitats. This is surprising because previous studies have indicated that arthropod communities vary in composition based on factors assessed in this study, such as humidity (Hamřík et al, 2023;Pelini et al, 2014) or density of vegetation (Neves et al, 2023;Pendleton et al, 2011), providing evidence that different mechanisms in heterogeneous landscapes shape different arthropod groups. Perhaps, the difference in abundance of these fruit-feeding butterflies may be associated with other habitat characteristics, such as canopy coverage (Hendy et al, 2020;McCabe et al, 2019), which likely differs throughout heterogeneous urban landscapes.…”
Section: Impact Of Landscape Heterogeneity On Frugivorous Butterfly C...contrasting
confidence: 54%
“…Our study shows that habitat openness is important for generating differences in species richness and occurrence of ant species, and supports the hypothesis that habitat openness is a key driver of ant community structure (Andersen, 2019). There are many studies reporting on the effects of vegetation cover on ants (e.g., Neves et al, 2023; Oliver et al, 2016; Retana & Cerda, 2000; Schmidt et al, 2013), and as a result, there are many different interpretations of the concept of openness. Two recent definitions of openness are “level of vegetation cover” (Andersen, 2019) and, in response to Andersen (2019), “the amount of sun exposure on the ground” (Lessard, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For phylogenetic analysis, we obtained DNA sequences of ultraconserved elements (UCEs) for 357 of our 439 species (one representative of each), using the methodology detailed in Neves et al (2023). We then used these sequences to construct a maximum‐likelihood tree with IQTREE ver.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have analyzed the functional and/or phylogenetic diversity of communities of ants (Blaimer et al 2015, Smith et al 2015, Liu et al 2016, Arnan et al 2017, Agavekar et al 2019), a dominant insect group that regulates a wide variety of ecosystem services, such as seed dispersal, decomposition, nutrient cycling, and biological control (Del Toro et al 2012). Many of these studies have documented how the different dimensions of diversity vary among habitat types (Liu et al 2016, Agavekar et al 2019) or along environmental gradients (Smith et al 2015, Arnan et al 2017, Neves et al 2019, Neves et al 2023). Vertical stratification is a common feature of ant assemblages, especially in the tropics (Brühl et al 1998, Vasconcelos and Vilhena 2006, Wilkie et al 2010, Antoniazzi et al 2021, Leponce et al 2021, Leahy et al 2022, Xing et al 2023).…”
Section: Introductionmentioning
confidence: 99%